Analysis of Interest in Reading Narratives in Indonesian Language Subjects in Class V MI Masyhudiyah - Sherra Iswanda; Nanang Khoirul Umam (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
This study is motivated by a lack of interest in reading narratives in Indonesian language lessons for especially elementary school students at MI Masyhudiyah Giri. This study aims to determine the interest in reading in grade V MadraI Masyhudiyah Giri, to find out what factors cause the lack of interest in reading grade V students, to find out the role of the teacher in raising interest in reading of grade V students MI Masyhudiyah, and The Role of Schools in Encouraging Interest in Reading stories in grade V MI Masyhudiyah Giri Kebomas Gresik. The form of this research is descriptive research that uses observation, interviews, and questionnaires. This interview technique involved 10 students from class V representatives at MI Masyhudiyah. This interview was conducted in a structured manner. As a result, we found an internal factor that caused this problem lack of interest in reading narratives in grade V students of MI Masyhudiyah Giri were gender, internal desire, interest in visual media and electronic media. The findings of the classification of the text method of reading indicate an interest in reading narratives in Indonesian language lessons. The importance of improving narrative reading for students is to increase knowledge and broad insight.